Point of Care Lung Diagnostic in ICU – Our Experience with Bedside Lung Ultrasound - Naumovski, Filip; Kuzmanovska, Biljana (Springer International Publishing, 2022)
Lung ultrasound as a Point of Care (POC) diagnostic technique might be a helpful tool in clinical decision making in critically ill patients. The aim of this study is to present 6 months experience of using lung ultrasound as a point of care tool in ICU. We performed a retrospective study of clinical records in patients with respiratory failure hospitalized in the ICU. The examination was made according to the BLUE Protocol (1). LUS was used in 48 out of 180 patients (26.6%). Pathological findings were noted in 42 patients (87,5%). Pleural effusion was detected in 10 patients (23.8%). Signs of interstital syndrome were detected in 21 patients (50%). Two patients (4.7%) had pneumothorax. Lung consolidation was detected in 18 patients (42.8%); 8 patients (44.5%) with pneumonia and 10 patients (55,5%)with atelectasis. According to the results of the LUS in 19 patients (45.3%) some sort of invasive procedure was undertaken. In 7 patients (36,8%) thoracic drainage was performed and bronchoaspiration in 4 patients (21%). In 12 patients (63.1%), mechanical ventilation was initiated. POCLUS is a helpful tool for rapid assessment of underlying pathological substrate in critically ill patients with acute respiratory failure having important role in clinical decision making.
Keywords: Point of care; Lung ultrasound; Critically ill